Research progress in abnormal carbohydrate, lipid, and protein metabolism in children with isolated growth hormone deficiency - Zhao, Tingting; Ma, Yan; Zheng, Zhimin; Zhang, Panpan; Sun, Hao (Frontiers in Endocrinology, 2025)
IntroductionGrowth hormone deficiency (GHD) is a rare endocrine disorder characterized by reduced or insufficient secretion of growth hormone (GH). GHD manifests with a heterogenous spectrum of symptoms mainly affecting musculoskeletal and endocrine system, with an increased predisposition to psychosocial disorders and ultimately reduced quality of life.MethodWe searched the main databases for studies describing the metabolic effects of growth hormone and its deficiency. All full-text articles and major reviews were manually searched for additional studies.ResultMetabolic derangements of GHD are reported in carbohydrate (insulin resistance, diabetes mellitus), lipid (hypercholesterolemia, hypertriglyceridemia), and protein (decreased lean body mass) metabolism. Currently, recombinant growth hormone (rhGH) replacement therapy is the primary standard of care for the treatment of GHD. Understanding the impact of GH, including the effect of GHD and rhGH therapy, on metabolism would be a critical step in development of effective treatment and selecting the best management strategies.DiscussionThis article reviews research progress and aims to offer new perspectives on the metabolic state of patients suffering from GHD and to compile data about the impact of rhGH therapy on metabolic pathways.